Pencegahan Perilaku Menyimpang Akibat Penyalahgunaan Narkoba pada Remaja Millenial di Pulau Untung Jawa - Aulia Nursyifa (Jurnal Pengabdian Pada Masyarakat, 2020)
PREVENTION OF DEVIANT BEHAVIOUR DUE TO DRUG ABUSE IN MILLENIAL ADOLESCENTS IN UNTUNG JAWA ISLAND. The changing times are so rapidly that youth are susceptible to deviating behaviors, one of which is drug abuse among adolescents. The existence of tourist attraction becomes an attraction for tourists in Pulau Untung Jawa, the tourists can bring influence to the youth in Untung Jawa island including drug use. The purpose of this devotion is to provide knowledge to the youth to make precautions against deviant behavior due to drug abuse. Method of community devotion in the form of counseling to adolescent youth organization Untung Jawa Island which amounted to 30 people. The results of devotion to the community showed that there was increased understanding of participants related to drug hazards of 82%. The participants were also very enthusiastic to follow the activities that took place. With the activity of devotion to the community can provide awareness for adolescents to do prevention of the impact of the drug by conducting a variety of positive activities such as: following entrepreneurial training, attending sports activities, attending the arts, following religious activities, becoming a janitor, and developing tourism objects in the Untung Jawa Island. This effort is a preventive measure of deviant behaviour due to adolescent drug abuse. The youth of Untung Jawa Island has proved to be a healthy generation without drugs and a young generation that is useful to the surrounding community.